Determinantes de la intención de compra por internet en consumidores bolivianos - Cáceres Fernández, Sandra Lorena (2022)
It has been seen that online shopping has been on the rise and companies have increased the virtual offer for purchases of their products and services. However, the reasons that influence this purchase intention on the Internet is necessary to know to achieve that advertising from companies is much more focus on the aspects that influence the most consumers. For this reason, the present research evaluates the influence of trust, through satisfaction and attitude towards online purchases, on the intention to purchase online; Likewise, the influence of post-use utility, through the convenience motivation, on online purchase intention was evaluated. 200 Bolivian consumers were surveyed using an online questionnaire with a 5-point Likert scale. The data was analyzed by modeling structural equations with partial least squares (SEM-PLS). The mean extracted variance of the study variables were found: convenience motivation (0.738), post-use utility (0.737), attitude towards online purchases (0.769), online purchase intention (0.811), satisfaction (0.668) and trust (0.715). Discriminant validity was evidenced using the Fornell-Larcker criterion. It was found that trust had an effect on satisfaction (0.794), trust had an effect on attitude towards online shopping (0.330), satisfaction had an effect on attitude towards online shopping (0.534) and attitude towards online shopping had an effect on online purchase intention (0.493); Likewise, the utility of use had an effect on the convenience motivation (0.686), the convenience motivation had an effect on the intention to buy online (0.199); finally, utility of use had an effect on online purchase intention (0.202). It could be demonstrated by the bootstrapping test that the positive relationship between the variables was significant. The seven hypotheses raised were accepted. This research will help companies to make decisions that can influence the variables and can improve advertising that helps increase the purchase of products and services online.